Faktor - Faktor yang Berhubungan dengan Kepatuhan Ibu Hamil Mengkonsumsi Tablet Zat Besi (Fe) di Wilayah Kerja Puskesmas Nambo Kecamatan Abeli Kota Kendari - Nofitasari, Ari; Selviana, Diana (Jurnal Gizi Ilmiah, 2016)
Iron is very useful for pregnant women in maintaining the stability of hemoglobin. Meanwhile, pregnant women in the Nambo Health Center Working Area in 2016, 9 of 12 mothers did not consume iron (Fe) tablets regularly, because after consuming iron (Fe) tablets they often felt nauseous and did not know about the function of the iron (Fe) tablet. and the benefits of iron (Fe) tablets, thus becoming the basis of this research. The purpose of this study was to determine the factors related to the compliance of pregnant women in consuming iron (Fe) tablets in the working area of ​​the Nambo Health Center, Kendari City. This type of research is observational with a cross sectional approach. The population in this study were all pregnant women who had their pregnancy checked and received Fe tablets from January to May 2016 at the Nambo Health Center in Kendari City in 2016 with a total of 115 people. With a simple random sampling technique, with a sample of 37 pregnant women. Based on the results of statistical tests with Fisher's Exach test obtained Knowledge (p = 0.001 smaller than = 0.05) which means there is a relationship, attitude (p = 0.002 is smaller than = 0.05) which means there is a relationship, Interaction Quality ( p = 0.009 is smaller than = 0.05) which means there is a relationship, family support (p = 0.006 is smaller than = 0.05) which means there is a relationship. It is recommended for the Puskesmas to further increase public knowledge, especially pregnant women about compliance or the importance of consuming iron (Fe) tablets.